STRATEGI PENGELOLAAN TAMBAK UDANG VANAME (Litopenaeus vannamei) TERHADAP SEBARAN PENYAKIT PARASITER DI KECAMATAN TANETE RIATTANG TIMUR - Dewi Virgiastuti Jarir; Anton Anton; Suryo Wirawan Anton; Yunarti Yunarti; Fatmah Fatmah; Jayadi Jayadi; Harlina Usman (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2020)
This research was conducted in August-September 2019 in three (3) subdistricts in Tanete Riattang Timur District, namely Waetuo, Panyula and Toro. The objectives of this study is to formulate priority management strategies for vaname shrimp ponds against the distribution of parasitic diseases. Data were collected by measuring water quality directly at each pond and interviewing shrimp farmers, Head of Marine and Fisheries Agency, fishery extension agents and lecturers of Marine and Fisheries Polytechnics of Bone in the field fish disease. Data were analyzed using both descriptive analysis and Process Hierarchy Analysis (AHP). The results showed that management of vaname shrimp ponds against parasitic diseases distribution was still lack of attention. Vaname shrimp pond management strategies against parasitic diseases distribution in the District of Tanete Riattang Timur, Bone regency, South Sulawesi was directed at the aspect of water quality. According to this study, the aspects to be improved were water quality management, education and experience of farmers, feed management, the use of SPF and SPR certified fries and biosecurity.